ASESMEN DIAGNOSTIK KETERAMPILAN 4CS DALAM PEMBELAJARAN MATEMATIKA KELAS AWAL: STUDI ANALISIS KEBUTUHAN [DIAGNOSTIC ASSESSMENT OF 4CS SKILLS IN EARLY GRADE MATHEMATICS LEARNING: A NEEDS ANALYSIS STUDY] - Lathifah Safiinatun Najaah; Febrisha Arya Amelia; Putri Miftakhul Rahmani (Universitas Pelita Harapan, 2026)
21st century learning requires students to possess 4Cs skills (Critical Thinking, Creativity, Collaboration, and Communication) as essential competencies to face technological developments and the challenges of the Society 5.0 era. However, among students in the early grades of elementary school, these skills have not been optimally identified, making diagnostic assessment necessary to determine students’ learning needs from an early stage. This study aimed to analyze the needs of 4Cs skills among first-grade students at SDN Polokarto 01 based on diagnostic assessment. This study employed a qualitative descriptive method supported by quantitative data. The subjects of this study were 14 first-grade students of SDN Polokarto 01 in the 2024/2025 academic year. The data of this study were obtained from the results of diagnostic assessments of 4Cs skills (Critical Thinking, Creativity, Collaboration, and Communication) in Mathematics learning on the topic of numbers 11–20. The diagnostic assessment used written tests, oral tests, and self-assessment techniques. The data were analyzed based on the Miles and Huberman model, namely data reduction, data display, and conclusion drawing. The results showed that the students’ 4Cs skills in the aspect of critical thinking were in the sufficient category, creativity was in the low category, collaboration was in the sufficient category, and communication was in the very good category. These findings indicate that the 4Cs skills of early-grade students are still varied; therefore, diagnostic assessment is important to be used as a basis for designing learning that is appropriate to students’ needs and characteristics. BAHASA INDONESIA ABSTRACT: Pembelajaran abad ke-21 menuntut peserta didik memiliki keterampilan 4Cs (Critical Thinking, Creativity, Collaboration, and Communication) sebagai bekal menghadapi perkembangan teknologi dan tantangan era society 5.0. Namun, pada peserta didik kelas awal sekolah dasar, keterampilan tersebut belum dapat terpetakan secara optimal, sehingga diperlukan asesmen diagnostik untuk mengetahui kebutuhan belajar peserta didik sejak dini. Penelitian ini bertujuan untuk menganalisis kebutuhan keterampilan 4Cs pada peserta didik kelas 1 SDN Polokarto 01 berdasarkan asesmen diagnostik. Penelitian ini menggunakan metode deskripsi kualitatif dan didukung oleh data kuantitatif. Subyek penelitian ini, yaitu 14 peserta didik kelas 1 SDN Polokarto 01 tahun ajaran 2024/2025. Data dari penelitian ini adalah hasil asesmen diagnostik 4Cs skills (Critical Thinking, Creativity, Collaboration, and Communication) pada mata pelajaran Matematika materi bilangan 11-20. Asesmen diagnostik ini menggunakan teknik tes tertulis, tes lisan, dan penilaian diri. Data dianalisis berdasarkan model Miles and Huberman, yaitu reduksi data, penyajian data, serta penarikan kesimpulan. Hasil dari penelitian ini menunjukkan bahwa kemampuan keterampilan 4Cs peserta didik kelas 1 pada aspek critical thinking berada pada kategori cukup, aspek creativity berada pada kategori kurang, aspek collaboration berada pada kategori cukup, serta aspek communication berada pada kategori sangat baik. Temuan ini menunjukkan bahwa keterampilan 4Cs peserta didik kelas awal masih bervariasi sehingga asesmen diagnostik penting digunakan sebagai dasar perancangan pembelajaran yang sesuai dengan kebutuhan dan karakteristik peserta didik.